2016
DOI: 10.1002/smll.201603420
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Processable, Air‐Stable Organic Nanoparticle–Carbon Nanotube Nanocomposites Exhibiting n‐Type Thermoelectric Properties

Abstract: Water-dispersed organic base nanoparticles are utilized for the highly stable n-type doping of single-walled carbon nanotubes in aqueous dispersion. Long-term stability is often a critical challenge in the application of n-type organic conductors. The present n-type organic materials exhibit almost no degradation in the thermoelectric properties over months, in air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 34 publications
3
48
0
Order By: Relevance
“…1). doping with each species [15]. It was found that while malachite green did partially ntype dope the SWCNTs, it wasn't capable of switching the semiconducting behaviour dramatically enough.…”
Section: Methods Of N-type Dopingmentioning
confidence: 99%
See 1 more Smart Citation
“…1). doping with each species [15]. It was found that while malachite green did partially ntype dope the SWCNTs, it wasn't capable of switching the semiconducting behaviour dramatically enough.…”
Section: Methods Of N-type Dopingmentioning
confidence: 99%
“…In this example, the sodium cation will 'seek out' the crown ether and complex in its centre where its charge is stabilised by the lone pairs of the oxygen molecules. Electron transfer reactions between dopant and SWCNT are key to n-type doping and are discussed in many papers on this subject [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. In its basic form, TPM-CB, possesses no such positive charge and is thus able to undergo electron transfer reactions with the nanotubes through both of its amine chains (Fig.…”
Section: Methods Of N-type Dopingmentioning
confidence: 99%
“…We consider the thermoelectric properties of CNT films for elucidating their electronics tates at specific doping levels. [27][28][29][30][31][32][33][34][35] These complementary characterizations reveal that ionic and neutral surfactants afford p-typea nd n-type CNTs, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…2000 S cm −1 from ca. 500 S cm −1 films . Along with this, recent studies suggested that the encapsulation of dopants into SWCNTs might enhance doping efficiency that afford enhanced conductivity …”
Section: Figurementioning
confidence: 84%
“…500 S cm À 1 films. [12][13][14][15][16][17] Along with this, recent studies suggested that the encapsulation of dopants into SWCNTs might enhance doping efficiency that afford enhanced conductivity. [18,19] Herein we introduce advanced molecular dopants for the encapsulation inside SWCNTs.…”
mentioning
confidence: 99%